Desarrollo de un microencapsulado de cedrón (Aloysia Citrodora), mediante secado por aspersión - Iglesias Chérrez, Daniela Lizbeth (2021)
This research designed a microencapsulation of cedron extract (Aloysia citrodora) by means of a unitary spray drying operation that uses encapsulating materials such as (maltodextrin and gum Arabic), which act as oxygen protectors to avoid oxidation. The studies of this technique have been increasing due to the need to protect the important material of the microencapsulation (extract) and on the other hand to the components such as heat and humidity, antioxidant capacity, stability and feasibility. The study elements were selected according to previously obtained research background, by means of optimization 9 runs were established and the control factors were: the feeding flow of 500 ml/h, 600 ml/h and 700 ml/h and air inlet temperature at 130 ºC, 140 ºC and 150 ºC. A response surface experimental design was applied using the Design Expert 8.0.6 program for processing the data obtained, and by optimizing the process, the optimum conditions were determined at an inlet air temperature of 150°C and a feed flow rate of 500 mL/h, obtaining a yield of 94.70%, humidity 3.845% and microencapsulation efficiency of 93.9%. In addition, the optimized microencapsulation was characterized having values of hygroscopicity 13 g/100g, bulk density 0.3213 g/ml, compact density 0.5712 g/ml, pH 5.24, angle of repose 34.30, solubility 92 %, Hausner's index 2.17, Car index 0.54, iron reducing antioxidant capacity (FRAP) 320.10 (µM Fe2/g sample) total polyphenols 0.12 mg/g.